Transformasi Etika Lokal Remaja Akibat Media Sosial di Desa Burangasi. - Itrali, La Itrali; Rahman, Hidayah (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2025)
Social media is the main trigger for changes in local ethics among teenagers in Burangasi Village, Lapandewa District. South Buton Regency. This study aims to find out the form of local ethics in adolescents in Burangasi Village who have changed due to social media and what efforts have been made to reduce the negative impact of social media on local ethical changes. The method used in this study is qualitative with ordinary observation techniques. In-depth observations, engaged observations, in-depth interviews and documentation. The results of the study show that social media has changed the local ethics of adolescents in Burangasi Village. This change is also realized by many parties such as parents, traditional leaders, teachers and the village government. Various efforts are also made to overcome the negative impact of social media on local ethics such as verbal reprimands for teenagers and the involvement of teachers in fostering local ethics, monitoring and monitoring local ethics, and the implementation of customary sanctions.